Ciclização eletrofílica intramolecular de (Z)-calcogenoeninos: síntese e reatividade de calcogenofenos e (Z)-calcogenetos vinilicos - Pistoia, Renan Piovesan (2019)
In the present thesis, efficient methods were developed to the synthesis of a series of heterocycles by electrophilic cyclization of (Z)-chalcogenoenynes 1, and chalcogenophenes 2, mediated by species of I2 and/or RSeBr. The first step of this thesis was the synthesis of a series (Z)-chalcogenoenynes 1, via the hydroselenation reaction, and the subsequent cyclization with I2 and/or RSeBr in dichloromethane as solvent and at room temperature. The reaction provided the products in high yields ranging from 28 to 87%. The synthesized products were subjected to coupling type reactions, such as Sonogashira and Suzuki, demonstrating the versatility of chalcogenophenes in the synthesis of different products highly functionalized in yields of 48-68% and 63%. Subsequently, it was possible to synthesize different chemo, stereo and regiosselective (Z)-vinyl chalcogenides, from the nucleophilic substitution reaction promoted by Na2X in the presence of organic halides and terminal alkynes. Through this protocol, it was possible to synthesize, in a satisfactory way (34 to 80% yields), a series of (Z)-vinyl chalcogenides using in situ generated hydroselenation conditions. In order to demonstrate the versatility of the synthesized products in addition to increasing their complexity structure, (Z)-vinyl chalcogenides were used in cross-coupling reactions, such as Suzuki, Kumada and Negishi.